The Relationship Between Antipsychotic-Induced Akathisia and Suicidal Behaviour: A Systematic Review - Kalniunas A (Dove Medical Press, 2021)
Arturas Kalniunas,1 Ipsita Chakrabarti,1 Rakhee Mandalia,1 Jasna Munjiza,2,3 Sofia Pappa1,2 1West London NHS Trust, London, UK; 2Division of Psychiatry, Imperial College London, London, UK; 3Central and North West London NHS Foundation Trust, London, UKCorrespondence: Sofia PappaRecovery Team East, Avenue House, 43-47 Avenue Road, London, W3 8NJ, UKEmail sofia.pappa@westlondon.nhs.uk; s.pappa@imperial.ac.ukObjective: We aim to systematically review evidence for a relationship between antipsychotic-induced akathisia and suicidal behaviour, in order to guide further clinical decision making in this area.Methods: Several electronic databases (Embase, Medline, Cochrane and PsychINFO) were systemically searched for articles published up to February 2021, using search terms related to akathisia, antipsychotics and suicidal behaviour. Two reviewers independently evaluated all the relevant studies using predetermined criteria and assessed the risk of bias for each included study. The systematic review was conducted in line with PRISMA methodology and reporting.Results: Following de-duplication, screening and application of exclusion criteria, four eligible studies were identified. All of the available studies were in English and included adult patients. Nevertheless, there was significant variability regarding methodology and overall quality was deemed low due to small sample sizes. There was insufficient data to perform statistical analyses of the results. Of the four studies, two found a weak correlation between antipsychotic-related akathisia and suicidal behaviour, a finding that was not supported by the remaining two studies.Conclusion: The search yielded very few studies for inclusion. On the basis of the existing evidence, akathisia cannot be reliably linked to the presence of suicidal behaviour in patients treated with antipsychotic medication. However, proactive screening for emerging suicidal behaviour in this vulnerable patient group is advisable. Our findings highlight the pressing need for further research in this area.Keywords: antipsychotic medication, akathisia, restlessness, suicidal behaviour